2020
DOI: 10.1080/1369118x.2020.1748086
|View full text |Cite
|
Sign up to set email alerts
|

Positive sentiments as coping mechanisms and path to resilience: the case of Qatar blockade

Abstract: Existing research on coping accentuates the role of positive emotions as defensive mechanisms to cope with stressful situations and the ensuing negative emotions. The same literature justifies the long-term effects of positive emotions that help build lasting resilience. Grounded in theories of coping and resilience, this paper (1) identifies the emotions that people actuate to cope with adversaries and (2) evaluates the resulting long-lasting adaptation and resilience. To do this, we examined the emotions fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
1
8
0
1
Order By: Relevance
“…If the progression of emotional symptomatology during confinement has not been studied extensively in the general population, as far as we know, this issue has not been addressed in parents of adolescents either. Studies have pointed to factors such as adequate pre-pandemic mental health ( Brailovskaia & Margraf, 2020 ); higher positive emotionality and lower negative emotionality, as well as high resilience, which might be helpful in the adaptation to isolation ( El-Masri et al, 2020 ). It should be borne in mind that the mental health of parents can have a significant impact on that of their children.…”
Section: Purposementioning
confidence: 99%
“…If the progression of emotional symptomatology during confinement has not been studied extensively in the general population, as far as we know, this issue has not been addressed in parents of adolescents either. Studies have pointed to factors such as adequate pre-pandemic mental health ( Brailovskaia & Margraf, 2020 ); higher positive emotionality and lower negative emotionality, as well as high resilience, which might be helpful in the adaptation to isolation ( El-Masri et al, 2020 ). It should be borne in mind that the mental health of parents can have a significant impact on that of their children.…”
Section: Purposementioning
confidence: 99%
“…The distinctive factors within the Qatari blockade are difficult to situate within the current perceived intergroup threat literature. This is due to a number of factors, chiefly the absence of violence, and the uniquely impactful role of social media in communicating some of the psychological effects of the blockade in young adults—living in an increasingly globalized Qatar—who have no direct experience of political conflict or violence ( Alkaabi and Soliman, 2017 ; El-Masri et al, 2020 ). Moreover, over 50,000 citizens from the Kingdom of Saudi Arabia, the Kingdom of Bahrain, and the United Arab Emirates lived in Qatar prior to the blockade, and significant overlapping familial, sporting, commercial and political ties existed across the Gulf ( Zahlan, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies confirm that the ratio of positive to negative affect has important implications for subjective well-being and flourishing [ 40 , 41 , 42 , 43 ]. The presence of positive affect also plays a key role as a coping mechanism, as it helps to deal with stressful situations [ 44 ] and can lead to building lasting resilience to better cope with future stressful events [ 45 , 46 , 47 ]. Moreover, results from positive affect enhancement interventions showed that changes in affect were also associated with changes in self-efficacy, job satisfaction, relationship satisfaction, and mental health [ 48 ].…”
Section: Introductionmentioning
confidence: 99%